MATH SOLVE

5 months ago

Q:
# Given the parent functions f(x) = 3x + 2 and g(x) = 5x − 10, what is g(x) − f(x)? g(x) − f(x) = 5x − 8 − 3x g(x) − f(x) = 5x − 12 − 3x<-------------------- g(x) − f(x) = 3x − 8 − 5x g(x) − f(x) = 3x + 12 − 5xPoints earned on this question: 2

Accepted Solution

A:

B IS YOUR ANSWER

(PROOF)

f(x) = 3x + 2

g(x) = 5x - 10

g(x) - f(x) = (5x - 10) - (3x + 2)

g(x) - f(x) = (5x - 3x) + (-10 - 2)

g(x) - f(x) = 2x - 12

(PROOF)

f(x) = 3x + 2

g(x) = 5x - 10

g(x) - f(x) = (5x - 10) - (3x + 2)

g(x) - f(x) = (5x - 3x) + (-10 - 2)

g(x) - f(x) = 2x - 12